Bone biomarkers in post-polio clinic patients - Madani, Seyed Pezhman; Kremer, Richard; Grunbaum, Ami; Bagmar, Shaddam; Benedetti, Andrea; Trojan, Daria A. (Frontiers in Endocrinology, 2025)
IntroductionOsteoporosis is common in post-polio clinic patients, and is reported in 30%to 50% of middle-aged individuals with previous polio. The levels of bone biomarkers (calcium regulating hormones, bone metabolism markers, and bone turnover markers), and the response of bone turnover markers to bisphosphonates is unknown in post-polio patients with osteoporosis.Objectives1) To describe serum levels of bone biomarkers in post-polio clinic patients with osteoporosis and compare these levels to those in controls with osteoporosis without neurological disease. 2) To examine the change in serum levels of bone biomarkers in post-polio patients following at least six months of treatment with bisphosphonates and compare these changes to controls.MethodsWe conducted a retrospective chart review of Post-Polio and Bone Metabolism Clinic charts of our center. Patients without osteoporosis, and incomplete lab data were excluded. For the second objective, patients untreated with bisphosphonates were excluded.ResultsMean age and proportion of females were similar in post-polio patients (n=25) and controls (n=31) (66.3 ± 8.1 vs 66.2 ± 10.9 years, 52% vs 61%). Mean baseline serum levels of calcium, calcium regulating hormones [parathyroid hormone (PTH), 25-hydroxy Vitamin D), and serum bone turnover makers (sBTM’s; osteocalcin, C-telopeptide, non-specific alkaline phosphatase (ALP)] were normal. PTH (4.4 ± 1.7 vs 5.5 ± 2.3 pmol/L, p=0.05), ALP (63.9 ± 15.8 vs 76.2 ± 26.7 U/L, p=0.04), osteocalcin (18.3 ± 8.8 vs 26.9 ± 8.4 ng/ml, p<0.01), and C-telopeptide (0.35 ± 0.2 vs 0.55 ± 0.21 microgram/L, p=0.01) were significantly lower in post-polio patients. After ≥ six months of treatment with bisphosphonates, sBTM’s declined significantly in both groups, with a significantly greater reduction in controls for osteocalcin (p<0.01) and C-telopeptide (p=0.02).ConclusionsWhile mean levels of all evaluated bone biomarkers were normal, PTH and sBTMs were significantly lower in post-polio patients with osteoporosis compared to controls, indicating reduced bone turnover. With bisphosphonate treatment, osteocalcin and C-telopeptide declined significantly in both groups, but significantly more in controls than in post-polio patients. These results indicate that BTM’s could be useful for monitoring treatment response in post-polio patients.